1995
DOI: 10.1104/pp.107.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of the Inducible Chlorella HUP1 Monosaccharide-H+ Symporter and Cloning of a Co-Induced Galactose-H+ Symporter

Abstract: l h e unicellular green alga Chlorella kesslerican induce monosaccharide-H+ symport catalyzing the energy-dependent transport of o-glucose (D-GIc) and several other pentoses and hexoses across the plasmalemma. l h e gene coding for the inducible HUPl monosaccharide-H+ symporter has been cloned and the protein has been characterized previously. l h e data presented in this paper demonstrate that the presence of the H U P l gene product alone is not sufficient to cover the broad substrate specificity of monosacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…They were designated HUP2 and HUP3 due to their high homologies to the HUP1 transporter (74 and 92%, respectively). Comparison of HUP1 and HUP2, both functionally expressed in S. pombe YGS-B25, showed that the transporters differ significantly concerning their substrate specificity [9]. All the previously identified residues of HUP1 probably involved in the glucose recognition/transport (see above) are also present in HUP2.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…They were designated HUP2 and HUP3 due to their high homologies to the HUP1 transporter (74 and 92%, respectively). Comparison of HUP1 and HUP2, both functionally expressed in S. pombe YGS-B25, showed that the transporters differ significantly concerning their substrate specificity [9]. All the previously identified residues of HUP1 probably involved in the glucose recognition/transport (see above) are also present in HUP2.…”
mentioning
confidence: 90%
“…Recently, it has been demonstrated that indeed two other monosaccharide/H ÷ symporters are co-induced by glucose [9]. They were designated HUP2 and HUP3 due to their high homologies to the HUP1 transporter (74 and 92%, respectively).…”
Section: ! Introductionmentioning
confidence: 99%
See 3 more Smart Citations